Archidamus' and Pericles' Foreign Policies: An Application of International Relations Theory - Hoggatt, Logan (My University, 2008)
In 431 B.C.E., with the outbreak of the Peloponnesian War, the Greek world entered into the most violent, divisive, and overall devastating conflict of its history. Myriad scholars have attempted to explain the causes of this catastrophic war, the reasons for the course it ultimately took, and the forces at work that impeded the peace process, the result of which is a robust body of literature that has substantially increased our knowledge of the war. However, a new perspective, focusing primarily on key individuals and making use of international relations theory, will give rise to novel explanations to the above issue. Specifically, the paper explores the foreign policies of two early Peloponnesian War leaders?the Spartan King Archidamus and the Athenian general Pericles. The application of international relations theory to the lives of these leaders and the exclusive focus of the paper on foreign policy offers a unique perspective and some new considerations to ponder.
Keywords: Greece--Foreign relations--To 146 B.C.; Pericles, 499-429 B.C.; Archidamus, II, d. 427 B.C.; Greece--History--Athenian Supremacy, 479-431 B.C.; Greece--History--Peloponnesian War, 431-404 B.C.